Bruised Inside Out: The Adverse and Abusive Life Histories of Incarcerated Women as Pathways to PTSD and Illicit Drug Use. (19th September 2018) - Jones, Melissa S.; Worthen, Meredith G. F.; Sharp, Susan F.; McLeod, David A.
Abstract : The majority of incarcerated women who suffer from diverse traumatic life histories including abusive home lives and intimate partner violence (IPV), develop post-traumatic stress disorder (PTSD) and struggle with heavy illicit drug use. While many have offered examinations of these relationships, the current study is among the first to utilize an integrated feminist pathways and general strain theory (GST) approach to explain them. Using data from a stratified random sample of all incarcerated women in Oklahoma ( N = 334), we explore the links between, adverse childhood experiences, including physical, sexual, emotional, and childhood neglect, IPV, PTSD, and heavy illicit drug use. Our findings indicate that the effects of IPV on heavy illicit drug use are mediated by PTSD symptoms suggesting that PTSD plays a significant role in the pathway to illicit drug use among Oklahoma women prisoners. Implications for the importance of utilizing an integrated feminist pathways and GST approach in future research are offered.